Orthodontic-Related Quality of Life in Patients with Palate and Lip Cleft - Parastoo Namdar; Naghme Khoshrang; Azam Haddadi Kohsar; Abolfazl Hossein Nataj (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: Palate and lip cleft are prevalent congenital deformities in children that have a multi-factorial etiology involving both genetic and environmental factors. The present study assessed the orthodontic-related quality of life in children with palate and lip cleft. Materials and methods: This descriptive cross-sectional study was conducted in 83 people with palate and lip cleft attending private dental clinics in Sari, Iran. They were selected via convenience sampling. Orthognathic quality of life questionnaire was completed by patients. The validity and reliability of the questionnaire is confirmed. The quality of life of the participants was determined from different dimensions, including social aspects, dental-facial beauty, oral function, and awareness of dental-facial beauty. One-way analysis of variance, t-test, and Pearson's correlation coefficient were used to analyze the data. Results: The study included 41 girls and 42 boys with mean age of 12.46 years (8-18 years of age). The frequency of cleft lip and palate, cleft lip, and cleft palate were 49.4%, 22.9%, and 27.7%, respectively. The study showed no significant difference between patients with different types of cleft lip and palate in terms of the total score for quality of life and its dimensions (P=0.02). We found no significant relationship between age and dimensions of quality of life (P<0.05). Age was found to be weakly correlated with the scores of the awareness domain (r=0.24, P=0.02). Conclusion: The quality of life was found to be at an average level in the population studied. The quality of life was not different between patients with cleft lip or palate.